اللغة في التراث العربي والغرب عند اللغويين القدماء والحديث - Nuruddin, Ahmad; Dzulhijjah, Siti Khoirotin; Rufaiqoh, Elok (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This research was conducted to find out the reality of the Arabic language in the Arab heritage and in the West. We are also known as the most advanced and modern linguistic scholars in the Arab heritage and the West. One of the objectives of this research is to describe how the opinions of linguistic scholars regarding the concept of language for ancient and modern linguists and the theory of the emergence of language for them in the Arab heritage and the West. The researcher adopted his approach on the qualitative or qualitative research approach and his type of research, which is desk research. As for the method of collecting data from this research, it is the analysis of documents, as they are based on the writing of past phenomena or incidents, and they may be paper or electronic. The method of analyzing his data is the method of content analysis, which is the method used to analyze scientific data from the content of the information contained in the data. As for the results of this research, the language has various definitions issued by ancient and modern linguists and from the Arab heritage and the West, and the theories of its origin are based on different and conflicting opinions between ancient linguists and modern linguists.